The Aging Tsunami and Senior Healthcare Development in China. Issue 8 (5th July 2018) - Li, Xin; Fan, Li; Leng, Sean X.
Abstract : China faces an aging tsunami. By the end of 2016, the number of older adults aged 60 and older reached 230 million. This number is projected to reach 418 million by 2035 and peak at 487 million by 2053. The number of individuals aged 80 and older, the oldest adults, reached 26 million and continues to grow by 1 million a year. The socioeconomic context, characterized by an inverted pyramid family structure and the number of "empty nesters, " has greatly compromised traditional Chinese family support for older adults. This article aims to provide an overview of geriatrics development in China. It begins with a brief account of the dramatic demographic shift, major socioeconomic factors, China's healthcare system, and reform related to senior health with a historical perspective. It then describes recent advances in government policy and support and development of a geriatrics physician workforce, care models, primary care networks, and privately owned senior care facilities and support services. Although it is impossible to cover all aspects of the topic, it is hoped that this article provides readers an overall picture of Chinese geriatrics and senior healthcare development in a complex and evolving healthcare system. Geriatrics communities in the United States and around the world will undoubtedly learn and benefit from the unparalleled and continued efforts to address this unprecedented opportunity and challenge in China.